Perluasan Kompetensi Absolut Peradilan Tata Usaha Negara Dalam Keadaan Darurat Bencana Non Alam di Indonesia - Amancik Amancik; Beni Kurnia Illahi; Putra Perdana Ahmad Saifulloh (Nagari Law Review, 2021)
The Indonesian government in dealing with the COVID-19 has created various legal instruments for policy implementation. One of those instruments is the Government Regulation in Lieu of Law Number 1 of 2020 which regulates the financial policy for COVID-19 which has been passed as Law Number 2 of 2020. However, there is a provision that is contrary to the administrative law principles, precisely in Article 27 paragraph (3). The norm is considered to close the gap of public access to take legal remedies to correct or examine decisions that have potential to cause harm related to actions or decisions. Even though Article 49 of Law Number 5 of 1986 also provides the similar meaning, however because the COVID-19 pandemic is categorized as a non-natural disaster, the COVID-19 Financial Policy Law should provide an expansion of state administrative court's (PTUN) absolute competence in examine and adjudicate administrative dispute cases. Therefore, this study tries to parse how the Regulations and Options for Public Legal Remedies towards Government Actions and Decisions in Non-Natural Disaster Emergencies in Indonesia. Second, what is the idea for expanding the absolute competence of PTUN in non-natural disaster emergencies in Indonesia. This research uses normative legal research methods with descriptive research specifications and analyzed through literature study and data analysis methods using juridical-qualitative. The result shows that it is time for redesigning in order to fulfill the community legal means in dealing with non-natural disaster conditions of COVID-19. The design can be rearrange the provisions in the COVID-19 Financial Policy Law and the Law of PTUN, so that the capability of PTUN in the future is not limited to state administrative decisions, including all the actions of state administrative bodies / Officials based on public law that cause harm for a person or civil legal entity either in normal conditions or in conditions of non-natural disasters